Psychological Impact of COVID-19 on Ophthalmologists in Iran - Masomeh Kalantarion; Zhale Rajavi; Hamideh Sabbaghi; Bahareh Kheiri; Mohammad Hasan Shahriari; Farinaz Fatahi Mozafar (Journal of Ophthalmic & Vision Research, 2022)
Abstract Purpose: To identify the psychological impact of coronavirus disease on ophthalmologists practicing in Iran between August and December 2020. Methods: In this cross-sectional online survey, a standard Patient Health Questionnaire- 9 (PHQ- 9) was completed by 228 ophthalmologists who were practicing in Iran. The PHQ- 9 questionnaire was revised by adding two additional questions specifically applicable for the assessment of the psychological impact of coronavirus disease on the Iranian ophthalmologists. An organized classification regarding the assessment of different depression severities identified as no (0–4), mild (5–9), moderate (10–14), or severe (15–21) was then considered for data analysis. Results: The mean age of our participants was 49.0 ± 15.61 years and the majority of them (67.1%) were male. Depression was discovered in 73.68% (n = 168) with different severities ranging from mild (n = 61, 26.75%), moderate (n = 63, 27.63%), and severe (n = 44, 19.3%). It was found that participants with depression were older as compared to those without depression (P = 0.038). Higher percentages of severe depression were noticed in the high-risk regions contaminated with corona virus as compared to the other low-risk regions (P = 0.003). Based on multivariable models, we determined that ophthalmologists who were somewhat concerned about their training/ profession (OR: 0.240; 95% CI: 0.086–0.672; P = 0.007) and those with no concerns about their income had lower association with depression (OR: 0.065; 95% CI: 0.005–0.91; P = 0.042). Conclusion: High prevalence of depression was observed among older aged Iranian ophthalmologists living in high-risk contaminated regions who possessed serious concerns with respect to their training/profession and income. It is recommended that the health policymakers of Iran pay more attention to the ophthalmologists who experience the aforementioned factors.